Assessing climate change impacts on extreme hydrological characteristics of reservoir inflow in Tianshan Mountain Range, China - Xiaobo Yun; Jianwen Wang; Hongjun Bao (Scientific Reports)
Abstract The hydrological extremes, caused by increasing regional extreme precipitation and melting glaciers or snow under climate change, pose a major challenge to reservoir management in Tianshan Mountain Range of China. Modeling and assessment of hydrological extremes are important measures to ensure the safety of reservoir operations and regional water resources. However, insufficient assessment of hydrological extremes faced by reservoirs in Tianshan Mountain Range has limited the development of flood risk assessment and early warning methods for mountain reservoirs. To this end, based on the VIC-CAS-R model that coupled with glacier snowmelt and reservoir modules, this study analyzed and evaluated the changing characteristics of precipitation and streamflow of selected mountain reservoirs in Tianshan Mountain Range from 1961 to 2014, and the Standardized Streamflow Index (SSI) and Mann-Kendall test were used to identify hydrological extremes as well as the changing trends. The result indicated that (1) the precipitation and streamflow of reservoirs in Tianshan Mountain Range showed a segmented change trend of “increasing-decreasing-increasing”; (2) The hydrological extremes of reservoirs in Tianshan Mountain Range showed notable variations in temporal and spatial distribution, reservoirs located in the western area faced a decrease in wet hydrological extremes (up to 70.8%) and an increase in dry hydrological extremes (up to 73.9%), while reservoir in the eastern region experienced a simultaneous increase in dry and wet hydrological extremes (up to 119.8%). These insights help to deepen the comprehension of the changing characteristics of hydrological extremes induced by climate change in Tianshan Mountain Range reservoirs, and provide support for predicting hydrological extremes in other arid inland mountain regions.